Direct photocoagulation to leakage points to treat chronic macular edema associated with branch retinal vein occlusion: a pilot study - Sakimoto S (Dove Medical Press, 2014)
Susumu Sakimoto, Motohiro Kamei, Hirokazu Sakaguchi, Mihoko Suzuki, Nagakazu Matsumura, Kentaro Nishida, Kohji NishidaDepartment of Ophthalmology, Osaka University Graduate School of Medicine, Suita, Osaka, JapanSummary statement: Direct photocoagulation reduces the central foveal thickness (CFT) in cases with chronic branch retinal vein occlusion (BRVO) of longer than 12 months duration. Photocoagulation might be effective for chronic macular edema due to branch retinal vein occlusion.Background: The aim was to investigate the effect of direct photocoagulation for treating chronic macular edema associated with BRVO.Methods: This study was a noncomparative, pilot interventional case series. We examined the CFT and best-corrected visual acuity over 6 months in patients with BRVO treated with direct photocoagulation.Results: Sixteen eyes of 16 patients had been treated with direct photocoagulation (mean follow-up period, 20.5 months). The mean CFT decreased significantly (P<0.001) between the baseline (465 µm) and the final visit (304 µm). The mean (logarithm of the minimum angle of resolution equivalent) best-corrected visual acuity at the baseline was 0.39 and improved significantly (P<0.001) to 0.20 at the final visit.Conclusion: Direct photocoagulation to leakage points is beneficial for treating chronic macular edema associated with chronic BRVO of longer than 12 months duration.Keywords: branch retinal vein occlusion, macular edema, optical coherence tomography, photocoagulation, VEGF